2021
DOI: 10.1111/jce.15033
|View full text |Cite
|
Sign up to set email alerts
|

Optimal substrate modification strategies using catheter ablation in patients with persistent atrial fibrillation: 3‐year follow‐up outcomes

Abstract: Objectives This study aimed to assess the comparative efficacy of four ablation strategies on the incidence rates of freedom from atrial fibrillation (AF) or atrial tachycardia (AT) through a 3‐year follow‐up in patients with persistent AF. Background The optimal substrate modification strategies using catheter ablation for patients with persistent AF remain unclear. Methods Patients with persistent AF were enrolled consecutively to undergo each of four ablation strategies: (a) Group 1 (Gp 1, n = 69), pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Their ablation resulted in atrial tachyarrhythmia freedom in 73.1% of the patients at 1-year follow-up [ 123 ]. FIRM-guided ablation may also be superior to linear left atrial ablation and CFAE ablation regarding the recurrence of AF, as shown by Hsieh et al [ 124 ]. However, a meta-analysis of head-to-head studies comparing PVI with and without FIRM-guided ablation showed no statistically significant difference in atrial tachyarrhythmia recurrence at a mean 18.8 months of follow-up [ 125 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 97%
“…Their ablation resulted in atrial tachyarrhythmia freedom in 73.1% of the patients at 1-year follow-up [ 123 ]. FIRM-guided ablation may also be superior to linear left atrial ablation and CFAE ablation regarding the recurrence of AF, as shown by Hsieh et al [ 124 ]. However, a meta-analysis of head-to-head studies comparing PVI with and without FIRM-guided ablation showed no statistically significant difference in atrial tachyarrhythmia recurrence at a mean 18.8 months of follow-up [ 125 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 97%
“…This method can be used to determine which active sources significantly contribute to the perpetuation of fibrillation in the atrium. However, electrical rotor ablation, which identifies and ablates the AF driver as the causative mechanism of AF, has demonstrated a wide variability in its success rates (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%